2014
DOI: 10.1371/journal.pone.0102395
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein D Inhibits HIV-1 Infection of Target Cells via Interference with gp120-CD4 Interaction and Modulates Pro-Inflammatory Cytokine Production

Abstract: Surfactant Protein SP-D, a member of the collectin family, is a pattern recognition protein, secreted by mucosal epithelial cells and has an important role in innate immunity against various pathogens. In this study, we confirm that native human SP-D and a recombinant fragment of human SP-D (rhSP-D) bind to gp120 of HIV-1 and significantly inhibit viral replication in vitro in a calcium and dose-dependent manner. We show, for the first time, that SP-D and rhSP-D act as potent inhibitors of HIV-1 entry in to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 57 publications
2
40
0
3
Order By: Relevance
“…Similar effects have been seen with SP-D, which has direct antiviral effects via binding of HIV envelope glycoprotein 120 and inhibition of viral replication (5). It prevents viral entry into target cells (6), but also facilitates transfer of virus from DCs to T cells (7). A recent pilot study showed evidence of reduced serum SP-D levels with ART (8), pointing to a need for further investigation on the effects of ART on pulmonary homeostasis.…”
Section: Noncellular Defenses Surfactantmentioning
confidence: 86%
“…Similar effects have been seen with SP-D, which has direct antiviral effects via binding of HIV envelope glycoprotein 120 and inhibition of viral replication (5). It prevents viral entry into target cells (6), but also facilitates transfer of virus from DCs to T cells (7). A recent pilot study showed evidence of reduced serum SP-D levels with ART (8), pointing to a need for further investigation on the effects of ART on pulmonary homeostasis.…”
Section: Noncellular Defenses Surfactantmentioning
confidence: 86%
“…Researchers have confirmed that lectins inhibit virus entry [27,29,34,35], and each step of the viral entry pathway is a potential target for antiviral agents. We conducted virus attachment and penetration assays to assess whether RpSP-A also interfered with PRRSV entry.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the antiviral activity of SP-D, which has a primary structure that resembles that of SP-A, have been reported more frequently. SP-D had an inhibitory effect on HIV infection through inhibition of viral entry by affecting gp120-CD4 interactions [29]. Marine and colleagues demonstrated that recombinant porcine SP-D prevented the attachment of human seasonal H 1 N 1 and H 3 N 2 virus to receptors on epithelial cells of the upper respiratory tract [?…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in dendritic cells (DC), SP-A increases HIV uptake, through enhanced binding to gp120 and facilitates transfer of HIV from DC to CD4 + T cells (Gaiha et al 2008). SP-D is also able to bind to HIV gp120 and inhibit viral infectivity (Meschi et al 2005), whilst rfhSP-D was also able to bind to gp120 and prevent infection of Jurkat T cells, U937 monocytic cells and PBMC, and significantly suppress the HIV-1 induced cytokine storm in these cells (Pandit et al 2014). Interestingly, a direct protein-protein interaction between rfhSP-D and DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin) modulates the capture of HIV-1 and its transfer to CD4 + T cells, revealing a novel and distinct anti-viral mechanism against HIV-1 by SP-D (Dodagatta-Marri et al 2017).…”
Section: Sp-a and Sp-dmentioning
confidence: 99%